Utilization of the Defense Industry in Supporting the Duties of the Navy to Enforce the Law and Maintain Security in Indonesian Waters - Sutadi Nugroho, Sigit (Journal of Industrial Engineering & Management Research, 2022)
The geographical location of Indonesia is very strategic, which is between two continents and an ocean. Indonesia has become a very strategic maritime axis, both for various relations between countries and as a world trade route. However, Indonesia has another side, namely as a state sovereignty that must be defended and guarded from various kinds of threats both from outside and within the country. So that Indonesia must have the ability in the form of a reliable and adequate defense equipment system as the main defense tool to maintain the sovereignty of the territory of the Republic of Indonesia and safeguard the national interest from all threats, disturbances and challenges as well as obstacles from within and outside the country. To overcome this, the development of the defense industry in Indonesia is urgently needed. In this study, the main problem is how the law (law) can regulate the development of the defense industry as a strategic industry in Indonesia. The method used in this research is descriptive analysis with normative juridical which is used in analyzing a problem regarding the development of the Indonesian defense industry in facing threats and challenges as well as disturbances to the sovereignty of the Republic of Indonesia due to Indonesia's very strategic geographical location. The results of the analysis and study of the problems show that the Indonesian defense industry has a very strategic position in the industry where the defense equipment in Indonesia has an important role in maintaining the country's sovereignty. Although the law in its regulation has been stipulated in Law number 16 of 2012 concerning the Defense Industry in Indonesia, it is still not regulated with clear regulations that can even be said to be ad hoc, therefore of course not beneficial for the development and development and growth of the Indonesian defense industry. . Where the law is a medium of information to the public so that it can be a very good change in the future, in this case it can direct where the defense industry will be developed in Indonesia, so that it can create a reliable defense industry company in producing defense equipment to maintain the sovereignty of the Republic of Indonesia.